Early Performance of Hospital Value-based Purchasing Program in Medicare: A Systematic Review. Issue 8 (August 2020) - Hong, Young-Rock; Nguyen, Oliver; Yadav, Sandhya; Etzold, Emma; Song, Jihee; Duncan, R. Paul; Turner, Kea
Abstract : Background: Under the Affordable Care Act, the Centers for Medicare and Medicaid Services has greatly expanded inpatient fee-for-value programs including the Hospital Value-based Purchasing (HVBP) program. Existing evidence from the HVBP program is mixed. There is a need for a systematic review of the HVBP program to inform discussions on how to improve the program's effectiveness. Objective: To review and summarize studies that evaluated the HVBP program's impact on clinical processes, patient satisfaction, costs and outcomes, or assessed hospital characteristics associated with performance on the program. Design: We searched the MEDLINE/PubMed, Scopus, ProQuest database for literature published between January 2013 and July 2019 using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. Results: Of 988 studies reviewed, 33 studies that met the selection criteria were included. A small group of studies (n=7) evaluated the impact of the HVBP program, and no impact on processes or patient outcomes was reported. None of the included studies evaluated the effect of HVBP program on health care costs. Other studies (n=28) evaluated the hospital characteristics associated with HVBP performance, suggesting that safety-net hospitals reportedly performed worse on several quality and cost measures. Other hospital characteristics' associations with performance were unclear. Conclusions: Our findings suggest that the current HVBP does not lead to meaningful improvements in quality of care or patient outcomes and may negatively affect safety-net hospitals. More rigorous and comprehensive adjustment is needed for more valid hospital comparisons. Abstract : Supplemental Digital Content is available in the text.